2018
DOI: 10.1186/s40249-018-0431-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for schistosomiasis in an urban area in northern Côte d’Ivoire

Abstract: BackgroundSchistosomiasis is a water-based disease transmitted by trematodes belonging to the genus Schistosoma. The aim of this study was to assess the relationship between the prevalence of schistosomiasis and access to water, sanitation and hygiene (WASH) and environmental and socioeconomic factors in the city of Korhogo, northern Côte d'Ivoire.MethodsA cross-sectional study including 728 randomly selected households was conducted in Korhogo in March 2015. The heads of the households were interviewed about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 21 publications
8
26
0
1
Order By: Relevance
“…We also confirmed a link between hematuria and S. haematobium infection on the Barombi Kotto site whereby children with hematuria were more likely to be egg-positive than egg-negative (50 vs. 5%, respectively). This is consistent with several previous studies that have unequivocally established the association between S. haematobium infection and hematuria ( 1 , 8 , 17 , 25 ). Surprisingly, however, clinical signs usually associated with hepatointestinal schistosomiasis ( 17 , 25 ) such as abdominal pain, diarrhea, tiredness or rectal pain did not reliably associate with S. mansoni infection in Yoro.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We also confirmed a link between hematuria and S. haematobium infection on the Barombi Kotto site whereby children with hematuria were more likely to be egg-positive than egg-negative (50 vs. 5%, respectively). This is consistent with several previous studies that have unequivocally established the association between S. haematobium infection and hematuria ( 1 , 8 , 17 , 25 ). Surprisingly, however, clinical signs usually associated with hepatointestinal schistosomiasis ( 17 , 25 ) such as abdominal pain, diarrhea, tiredness or rectal pain did not reliably associate with S. mansoni infection in Yoro.…”
Section: Discussionsupporting
confidence: 93%
“…Risk factors of infection (reinfection and/or persistent infection) in these sites were similar to those previously reported ( 1 , 8 , 17 , 25 ) i.e. age, gender, frequency of contact with infested water ( 25 , 30 32 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…https://doi.org/10.1371/journal.pntd.0008266.g001 PLOS NEGLECTED TROPICAL DISEASES the only ones that were observed to swim. This is consistent with an activity survey in Côte d'Ivoire, which also found boys swam more than girls [46] and where girls spend more time at domestic tasks. However, in our study we observed fewer gender-specific occupational activities, whilst the activity survey found boys engaging more in fishing and watering cattle and girls spending more time at the market.…”
Section: Discussionsupporting
confidence: 89%
“…Schistosomiasis is the most widespread parasitosis in the world, affecting specially the population from underdeveloped or developing countries. It manifest most often in its most severe form, in individuals living in areas with poor basic sanitation (Andrade Filho, de Queiroz, dos Reis, Amaral, & Brito, 2015;M'Bra et al, 2018;Zoni, Catalá, & Ault, 2016).…”
Section: Introductionmentioning
confidence: 99%